2020
DOI: 10.2147/ijn.s244815
|View full text |Cite
|
Sign up to set email alerts
|

<p>Influence of Simvastatin-Strontium-Hydroxyapatite Coated Implant Formed by Micro-Arc Oxidation and Immersion Method on Osteointegration in Osteoporotic Rabbits</p>

Abstract: Enhancing osteointegration of implants in osteoporosis patients is a necessity since implantations frequently fail in these patients. The aim of this work is to study how simvastatin-strontium-hydroxyapatite coated implants perform in rabbits with osteoporosis. Materials and Methods: Crystalline HA and Sr-HA oxide film were prepared through micro-arc oxidation. Surface characterization including morphology, roughness, element composition, phase composition, hydrophilicity were then evaluated. Simvastatin loade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…So far, several in vitro studies on animal models have been developed to test the effectiveness of strontium-enriched hydroxyapatite bioceramics [ 63 , 64 , 65 , 66 ]. Research has confirmed the therapeutic potential of such materials, indicating their effectiveness in the regeneration of bone tissue, high biocompatibility, and improvement of osteogenic abilities.…”
Section: Strontium In the Treatment Of Osteoporosismentioning
confidence: 99%
“…So far, several in vitro studies on animal models have been developed to test the effectiveness of strontium-enriched hydroxyapatite bioceramics [ 63 , 64 , 65 , 66 ]. Research has confirmed the therapeutic potential of such materials, indicating their effectiveness in the regeneration of bone tissue, high biocompatibility, and improvement of osteogenic abilities.…”
Section: Strontium In the Treatment Of Osteoporosismentioning
confidence: 99%
“…The contact angle was lower when coating with GoHAP3 compared to GoHAP1. The results are important for biomedical applications, as the reduced water contact angle contributes to improved cell attachment, bone growth and bioactivity [66][67][68]. Values are given as mean ± SD.…”
Section: Contact Angle Measurement Of Coatingsmentioning
confidence: 99%
“…Recently, it is demonstrated that MAO results in the formation of a porous oxide layer on implant surfaces, further enhancing biocompatibility and bonding strength [ 16 ]. Furthermore, by adjusting the electrolyte compositions, various metal ion-doped coatings can be successfully constructed onto implant surfaces [ 17 ]. Various metal ions ( e.g.…”
Section: Introductionmentioning
confidence: 99%